Re-assessing the inner city of Johannesburg : an exploration into emerging African urbanism and the discovery of black agency in Phaswane Mpe's Welcome to our Hillbrow and Kgebetli Moele's Room 207 - O'Shaughnessy, Emma Vivian (Department of English Language and Literature, 2015)
Includes bibliographical references (leaves 121-131).